Given f(x) = ((x^2-3x)/(2x-3))* ln(x^2 -3x)
We can approach this by letting
f(x) = g(x)*h(x) f'(x) = g(x)*h'(x) + g'(x)*h(x) " " " " " " " " " " " (1)
color(red)(g(x) = ((2x^2 -3x)/(2x-3))" " " " " " " " (2)
color(blue)(h(x) = ln(x^2 -3x) " " " " " " " " "(3)
======================================
Let differentiate color(red)(g(x) = ((x^2-3x)/(2x-3)) using quotient rule
g'(x) = ((2x-3)(2x-3)-(2(x^2-3x)))/(2x-3)^2
g'(x) = [(4x^2 -6x-6x+9)-(2x^2 -6x)]/(2x-3)^2
g'(x) = [4x^2 -12x + 9 -2x^2 +6x]/(2x-3)^2
color(red)(g'(x) = [2x^2-6x+9]/(2x-3)^2 " " " " " " " " " " " (4)
Let differentiate color(blue)(h(x) = ln(x^2 -3x)
Note: f(x) = ln(x) hArr f'(x) = (dx)/x
color(blue)(h'(x) = (2x-3)/(x^2-3x) " " " " " " " " " " (5)
==============
Now we can put it together using (1)
f(x) = (x^2-3x)/(2x-3) * ln(x^2 -3x)
f'(x) = (x^2-3x)/(2x-3) * color(blue)((2x-3)/(x^2-3x)) + color(red)((2x^2 -6x+9)/(2x-3)^2) * ln(x^2 -3x)
f'(x) = cancel(((x^2-3x))/(2x-3) * color(blue)((2x-3))/(x^2-3x))+ color(red)((2x^2 -6x+9)/(2x-3)^2) * ln(x^2 -3x)
f'(x) = 1+ [color(red)((2x^2 -6x+9)/(2x-3)^2) * ln(x^2 -3x)]
f'(x) = ((2x-3)^2 + (2x^2 -6x+9)* ln(x^2 -3x)]/(2x-3)^2